SOME ANTECEDENTS OF THE SECURITIES AND EXCHANGE COMMISSION. - Taylor, J. R. (The Accounting Review, 1941)
Time and again the prosperity malpractices of corporate management were the subjects of erudite discussions. Moreover, the courts have always had a tendency toward setting up rules of law which they felt would protect the small absentee owner. Perhaps this depression philosophy may be said to be accountable for the desire to limit the capital raising activities of those large corporate entities in future prosperity periods, who had demonstrated themselves to be given to faulty procedures during the prosperity era of the twenties. But it must be emphasized that there was a trend toward such financial regulations even during the preceding prosperity period. Furthermore, during this period there were evidences indicating that the accountants responsibility would likewise expand and increase under this financial control philosophy. Perhaps the first forecast of accountants' increasing responsibility was the Ultra Mares case which began early in 1924. After 1922, however, corporate management turned to selling securities in order to secure the capital needed.